LFC and Reserve Prequalification for Synchronization with Continental Europe Synchronous Area - Deltuva, Ramūnas; Kriuglaitė, Miglė; Račkienė, Roma; Otas, Konstantinas (Electrical Engineering and Technology, 2025)
This paper presents a comprehensive analysis of the Load Frequency Control (LFC) framework required for the synchronization of Electric Power Systems (EPSs) with Continental Europe (CE). The study focuses on ensuring stable and reliable operation of autonomously functioning EPSs by examining technical requirements and prequalification procedures for Frequency Containment Reserve (FCR) and LFC-related reserves. Numerical simulations were performed to assess system dynamic behavior under disturbance conditions. The results indicate that following a 100 MW active power loss, system frequency decreased to 49.82 Hz and was restored to the nominal 50 Hz within 9 min using FCR and automatic Frequency Restoration Reserve (aFRR). A more severe 200 MW disturbance resulted in a minimum frequency of 49.68 Hz, requiring additional activation of manual Frequency Restoration Reserve (mFRR), with recovery achieved in 18 minutes. In extreme scenarios involving up to 600 MW power loss, the frequency dropped below the critical threshold of 49.2 Hz, but full restoration was achieved within 36 min through coordinated activation of FCR, aFRR, mFRR, and Replacement Reserve (RR). Long-term simulations demonstrated that the Frequency Restoration Control Error (FRCE) remained within the System Operation Guidelines (SOGL) Level 1 limit for 75% of the time and within the stricter Level 2 limit for 96%, meeting CE quality requirements. The study also evaluates prequalification procedures, including technical testing, communication validation, and energy management for Limited Energy Reservoir providers, ensuring robust and non-discriminatory participation in balancing markets.